1999
DOI: 10.1093/intimm/11.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive human T cell lines recognizing ribosomal protein L7

Abstract: Sera of patients suffering from systemic lupus erythematosus (SLE) frequently contain oligoclonal IgG autoantibodies with high affinity for the ribosomal protein L7 (rpL7). The humoral autoimmune response to rpL7 apparently is driven by antigen and T cell dependent. In order to analyze the T cell response to rpL7 we cultured peripheral blood lymphocytes of healthy individuals and SLE patients in the presence of recombinant rpL7. After 10 days, the cytokine response to re-stimulation with rpL7 was examined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…RPL7 , ribosomal protein L7, has been established as an autoantigen representing a frequent target for autoantibodies from patients with systemic autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis [28]. The humoral autoimmune response to RPL7 apparently is driven by antigen and is T cell dependent [29]. KCNB2 is a potassium voltage-gated channel expressed in a number of tissues, including gastrointestinal smooth muscle cells [30], [31].…”
Section: Discussionmentioning
confidence: 99%
“…RPL7 , ribosomal protein L7, has been established as an autoantigen representing a frequent target for autoantibodies from patients with systemic autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis [28]. The humoral autoimmune response to RPL7 apparently is driven by antigen and is T cell dependent [29]. KCNB2 is a potassium voltage-gated channel expressed in a number of tissues, including gastrointestinal smooth muscle cells [30], [31].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the initial work on RPL7 was stimulated by the observation that the protein was an autoantigen in human patients with systemic lupus erythematosus or other autoimmune diseases (Donauer et al, 1999). Down-regulation of rpl7 transcripts occurred in senescent human fibroblasts as compared with presenescent and quiescent cells (Seshadri et al, 1993) whereas DD-PCR revealed that rpl7 was one of several genes up-regulated esophagus squamous cell carcinoma (Kazemi-Noureini et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Its role in lupus is discussed in ref. [31]. In Figure 6 we see three, high Betti centrality nodes: RPL7, RPL7A and RPS19.…”
Section: Gibbs-homology Network Graph Showing Both Rps10 and Rps18 Asmentioning
confidence: 95%